The incidence of symptomatic deep vein thrombosis and pulmonary embolism, following THA in patients, with postoperative chemoprophylaxis in Indian population - Avulapati, Sandeep Krishna; Mahalingam, Senthil Kumar; Munirathnam, T.; Gudaru, Jagadeesh; Gudaru, Karthik (International Journal of Research in Orthopaedics, 2018)
Background: Deep vein thrombosis (DVT) and pulmonary embolism (PE) can occur in patients after elective total hip arthroplasties (THA). Indian population appears to have low incidence of DVT and PE in comparison with Western population due to difference in ethnicity, genetic make-up, social life styles. The study intends to find the incidence of symptomatic DVT and PE in postoperative THA patients. The aim of the study was to study the incidence of symptomatic DVT and PE, in post-THA patients in Indian Population. Methods: Retrospective study conducted from 1st January, 2017 to 31st July, 2018 in BIRRD (T) Hospital. All patients who underwent THA are included, after fulfilling inclusion and exclusion criteria. Patients were evaluated for symptoms during the hospital stay and after discharge for 3 Months. Results: Total number of patients who had THA were 447 (n=447). The symptomatic DVT was found in 1 (n=1) patient. He developed DVT (n=1) during the study period, in first 48 hours postoperatively and recovered with ICU management. The same patient showed symptoms of PE but recovered fully. All patients were on a prophylactic regimen. Conclusions: Our results suggest incidence of DVT and PE are low in the Indian population with a prophylactic regimen.